4q+3=q+3

Simple and best practice solution for 4q+3=q+3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4q+3=q+3 equation:


Simplifying
4q + 3 = q + 3

Reorder the terms:
3 + 4q = q + 3

Reorder the terms:
3 + 4q = 3 + q

Add '-3' to each side of the equation.
3 + -3 + 4q = 3 + -3 + q

Combine like terms: 3 + -3 = 0
0 + 4q = 3 + -3 + q
4q = 3 + -3 + q

Combine like terms: 3 + -3 = 0
4q = 0 + q
4q = q

Solving
4q = q

Solving for variable 'q'.

Move all terms containing q to the left, all other terms to the right.

Add '-1q' to each side of the equation.
4q + -1q = q + -1q

Combine like terms: 4q + -1q = 3q
3q = q + -1q

Combine like terms: q + -1q = 0
3q = 0

Divide each side by '3'.
q = 0

Simplifying
q = 0

See similar equations:

| x^4-8x^3+x-8=0 | | 12-8x=39-29x | | 35+33x=11x+12+22 | | -143-9x=9x+9x | | 3a-1=a+7 | | 7a+2=10 | | 3+5u=2u+12 | | 2x+7x^2=8 | | 6m-1=m+9 | | 2x+7x=4 | | x^3-3x-18=0 | | 4x*57=3x-7 | | 2x+2x+2=0 | | -7r+5=5r+35 | | -7r+4=5r+35 | | 2x^2+2x-10=0 | | 2x(3x+3)=18 | | x-5x=-5,682 | | 4x-2=2x+14 | | 4x-8=8x | | 2x+3=15+x | | 56x+(-5x+9x)= | | -1-2x=3 | | 4(2a+-1)+5(4+-2a)-3a=-4(5+2a)-4 | | 0.41=0.07x | | -14=x+22 | | 0.41=0.07 | | x-8.8=-3.3 | | 0.44=0.07x | | 0.27=0.07x | | 0.21=0.07x | | y-24=-5 |

Equations solver categories